Analysis of the evolution of the number of patents related to the milking process - Putti, Fernando Ferrari [UNESP]; Góes, Bruno César [UNESP]; Filho, Luís Roberto Almeida Gabriel [UNESP]; De Lucca Sartori, Diogo [UNESP]; Chacur, Marcelo George Mungai; Cremasco, Camila Pires [UNESP] (FapUNIFESP (SciELO), 2018)
The dairy economy is one of the most important sectors of Brazilian agribusiness. Dairy production showed growth over the last few decades, which can be attributed to factors such as: an increase in the number of milked cows and/or the adoption of more productive animals in the dairy herd, and the insertion of technology into the dairy production process. Thus, the objective of this study was to quantify, together with the Brazilian National Institute of Industrial Property-INPI-database, all registrations of patents related to the milk production activity, mainly during the milking phase, verifying if there is any correlation between the number of registrations and the increase in productivity and/or the increase in number of lactating animals. Patent records related to the milking process carried out between 1975 and 2015 were consulted in the INPI database. The Brazilian law No. 9, 279 was enacted in 1996, which guarantees the rights and obligations related to industrial property, and at that time a greater demand for registrations occurred, although this was not significant when compared with the period after 2006, when Normative Instruction 51 came into force, which regulates the whole process involved in milk production, obtaining a significant increase in the number of registrations in the INPI database. It was thus concluded that the increase in the number of patents during the period analyzed coincided with the increase in milk production, which was related to the greater number of milked animals and/or higher milk yields in the Brazilian herd, which makes the technological evolution in the sector be mentioned as one of the causes of the improvement in quality of dairy products.
Análise da evolução do número de patentes relacionadas ao processo de ordenha
Keywords: INPI; Milk.; Production; Technology